Pengembangan Sistem Informasi Terintegrasi Untuk Prediksi Persediaan Penjualan Lele Berbasis Machine Learning di Taman Wisata Jantipark - Didik Nugroho; Aninda Dyah Hayu Pinasti Putri; Bebas Widada; Raden Arie Febrianto; Sri Tomo (Journal of Information Technology, Computer Engineering and Artificial Intelligence (ITCEA), 2026)
Jantipark is a tourist destination managed by Janti Village, Polanharjo District. It is a water park that offers child-friendly swimming pools, as well as tourist attractions such as outbound activities, and is commonly used for Outing Classes. In addition to tourist attractions and swimming pools, it also provides food catering services. A wide variety of food is sold here. One of the menus consists of fried catfish and grilled catfish, which are commonly ordered as side dishes for dine-in visitors or taken home as souvenirs. The management has previously made efforts by preparing catfish stocks; however, the stock often deviates from actual demand or sales. This research develops a stock prediction system for sales. The data collection method used is observation, while the system development utilizes PHP, MySQL, and the Single Exponential Smoothing algorithm. System testing is conducted using MAPE. The research results show that the difference between the predicted outcomes and real demand is around 3.81%, indicating that the variance is not highly significant.